1016. Bloodstream Infection Survey in High-Risk Oncology Patients (BISHOP) With Fever and Neutropenia (FN): Predictors for Morbidity and Mortality. (26th November 2018) - Freifeld, Alison G; Zimmer, Andrea; Arnold, Christopher; Baddley, John W; Chandrasekar, Pranatharthi; El Boghdadly, Zeinab; Maziarz, Eileen K; Montoya, Jose G; Pergam, Steven; Rolston, Kenneth V; Satyanarayana, Gowri; Shoham, Shmuel; et al.
Abstract: Background: Blood stream infection (BSI) during neutropenia is associated with high risk for morbidity and mortality in patients with hematologic malignancies receiving chemotherapy or undergoing hematopoietic cell transplant (HCT). We sought to identify factors associated with increased risk for critical illness (CI) morbidities within 7 days of BSI with index FN following chemotherapy. Methods: A prospective ongoing survey among 14 high-volume US cancer centers submitting clinical and microbiologic data from consecutive HM patients with blood stream infection (BSI) during first FN after cytotoxic chemotherapy or HCT. We evaluated factors influencing poor outcomes defined as critical illness (need for pressor support, mechanical ventilation, new pneumonia or new BSI) within 7 days of BSI with index FN. Concordance between antibiotic and BSI isolate was determined by investigator (AZ, AF) interpretation of susceptibility reports provided by each center compared with the initial antimicrobial regimen (IAR) used, for single organism bacteremias only. Results: Among 294 FN bacteremic episodes (93 HCT) were 336 bacterial pathogens (48.5% Gram-negative [GN], 46.5% Gram-positive [GP], and 6% anaerobes). Death occurred in 11/294 (4%) and 41/294 (14%) had CI by day 8. At FN presentation, mean MASCC score of those with CI vs. those without was 16.9 vs. 18.6 ( P = 0.03) and there was a trend toward higher mean PITT scores for patients with CI by day 8 vs. those without (1.54 vs. 0.82 ( P = 0.08)). Among GN bacteremias, 15% developed CI vs. 14.5% in nonviridans group Streptococci (VGS) GP bacteremias, and 10.9% in VGS bacteremias (NS). Among patients with single organism bacteremias (88% of all BSI), mismatch of IAR coverage with isolate susceptibilities occurred in 16.7% (38/227). Among patients whom IAR was active vs. inactive against BSI isolate, 16% vs 14.3%, respectively, developed CI ( P = 0.81). Conclusion: These data indicate that the MASCC score applied to high-risk inpatients may be a predictor for CI in the first week after bacteremia FN. The PITT shows less correlation with poor outcomes. There was no association between isolate type (GN, GP, or VGS) and CI. Notably there was no association between mismatched BSI susceptibility and antimicrobial spectrum of the IAR and early CI. Disclosures: A. G. Freifeld, Merck: Investigator, Research grant. A. Zimmer, Merck: Investigator, Research grant. S. Pergam, Merck: Consultant, Consulting fee. Chimerix: Consultant, Consulting fee. K. V. Rolston, Merck: Investigator, Research grant. JMI Laboratories: Investigator, Research grant. Shionogi (Japan): Investigator, Research grant. S. Shoham, Merck: Investigator and Scientific Advisor, Consulting fee and Grant recipient. Astellas: Investigator, Grant recipient. Shionogi (Japan): Investigator, Grant recipient. Gilead: Investigator, Grant recipient. Shire: Investigator, Grant recipient. T. J. Walsh, Merck: Grant Investigator, Research grant. Atellas: Consultant, Grant Investigator and Scientific Advisor, Consulting fee and Research grant. Gilead: Scientific Advisor, Consulting fee. Allergan: Grant Investigator and Scientific Advisor, Consulting fee and Research grant. Scynexis: Grant Investigator, Research grant. Amplyx: Grant Investigator, Research grant. Shionogi: Scientific Advisor, Consulting fee. J. A. Young, GSK: Investigator, The University of Minnesota is reimbursed for contract costs associated with conducting clinical trials of vaccine. I receive no personal financial benefit. Y. Zhang, Merck: Investigator, Research grant. J. Meza, Merck: Investigator, Research grant.